Portraying Character Education in Junior High School Textbooks of the 2013 Curriculum - Dio Permana; Rita Inderawati; Machdalena Vianty (English Department - University of Sultan Ageng Tirtayasa, 2018)
It cannot be denied that character education is the key to avoid moral degradation. This study aimed at investigating character education in three English textbooks for Junior High School of the 2013 Curriculum. Content analysis technique was employed in this current study. The result of the study showed that character values Related to Self gained a very large majority percentage which obtained (56.69%). Then it was followed by character values Related to Others (32.83%) and a very small number of Related to Environment (8.30%), Related to Nation (1.42%) and Related to God (0.75%) as the least percentage occurrence. It also found that there were four additional character values namely Confidence, Courtesy, Wisdom, and Humility existed in the textbooks. These results lead to the conclusion that the textbook authors should reconsider the existence of 18 character values in each English textbook for Junior High School.Keywords: character education; content analysis; English textbook